2021
DOI: 10.3390/ijms22084152
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia, Lymphopenia-Induced Proliferation, and Autoimmunity

Abstract: Immune homeostasis is a tightly regulated system that is critical for defense against invasion by foreign pathogens and protection from self-reactivity for the survival of an individual. How the defects in this system might result in autoimmunity is discussed in this review. Reduced lymphocyte number, termed lymphopenia, can mediate lymphopenia-induced proliferation (LIP) to maintain peripheral lymphocyte numbers. LIP not only occurs in normal physiological conditions but also correlates with autoimmunity. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 196 publications
0
12
0
Order By: Relevance
“…The same ANCA can stimulate neutrophils to release NETs that include autoantigens and cause AAV patients to produce autoimmune responses to these components (29). At the same time, lymphocytopenia is considered to be related to inflammation burden, such as in rheumatoid arthritis, Crohn's disease, systemic lupus erythematosus, and vasculitis (30)(31)(32)(33). However, some studies found that lymphocytes are negatively correlated with the recurrence rate, with lymphocytopenia associated with a lower recurrence rate (34).…”
Section: Discussionmentioning
confidence: 99%
“…The same ANCA can stimulate neutrophils to release NETs that include autoantigens and cause AAV patients to produce autoimmune responses to these components (29). At the same time, lymphocytopenia is considered to be related to inflammation burden, such as in rheumatoid arthritis, Crohn's disease, systemic lupus erythematosus, and vasculitis (30)(31)(32)(33). However, some studies found that lymphocytes are negatively correlated with the recurrence rate, with lymphocytopenia associated with a lower recurrence rate (34).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the potential mechanism of influenza and SARS-CoV induced lymphopenia could be distinguished. Up to now, it has been presumed that lymphopenia detected in cases of respiratory virus diseases might be due to inhibition of thymus for T-cell generation, abnormal cell death, tissue sequestration of lymphocytes, exhaustion, migration or homing from blood [ 34 , 35 ]. In particular, lymphopenia of severe influenza but not SARS patients could be a consequence of a direct infection in T cells and infection-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A link between lymphopenia and autoimmunity has been reported 51 . Under lymphopenic conditions, the compensatory expansion of T cells exhibiting innate T cell/T FH cell profiles, converts these cells into pathogenic effectors [52][53][54] .…”
Section: Discussionmentioning
confidence: 99%